Envy, poison, and death : women on trial in ancient Athens - Eidinow, Esther (Oxford University Press, 2016)
This volume explores three trials conducted in Athens in the fourth century BCE; the defendants were all women charged with undertaking ritual activities, but much of the evidence remains a mystery. The author reveals how these trials provide a vivid glimpse of the socio-political environment of Athens during this time